The influence of promotional attractiveness and product quality on the willingness to repurchase consumers of scarlett whitening body lotion - Zed, Etty Zuliawati; Purnamasari , Pupung; Amaruddin, Hamdan (Proceeding International Pelita Bangsa, 2023)
Beauty trends about facial and body skincare are on the rise these days. This makes the beauty industry grow rapidly. Along with the development of the times, the desires and needs of consumers for beauty care products are also growing, in addition to facial care, the most concerned thing by every woman is body care. Body care is a series of body treatments used to keep the body's skin condition healthy and well-groomed, the use of body lotion is included in a series of body treatments, one of the beauty products that is currently on the rise is body lotion from Scarlett Whitening. The purpose of this study was to determine the effect of promotion and product quality on the willingness to repurchase scarlett whitening body lotion products. Respondents in this study were consumers who had bought Scarlett Whitening body lotion products. The sampling technique used is non-probability sampling using Judgemental sampling with a sample of 130 respondents. The data analysis techniques used are validity test, reliability test, classical assumption test, multiple linear regression analysis, t test, F test and determination coefficient. The results of this study found that the promotion variable has a proven positive effect on willingness to repurchase directly, and the product quality variable has a positive effect on willingness to repurchase directly.